Management procedures for sustainable development (applicable to municipalities, micro-regions and river basins) (UN. ECLAC SantiagoCL, 1995)
Provides a conceptual framework which makes it possible to organize the multiple inputs to the environmental issue, with the aim of reaching sustainable development.
DC